Learning agrobiodiversity: options for universities in Sub-Saharan Africa: Proceedings of a regional workshop, 21-23 January 2009, Nairobi, Kenya - Rudebjer, P.G.; Schagen, Boudy van; Chakeredza, Sebastian; Kamau, H. (2009)
Agrobiodiversity needs to enter university curricula in a broader fashion, to prepare graduates for both conserving and using agrobiodiversity sustainably. To tackle this issue, the first regional consultation on agrobiodiversity education in Sub-Saharan Africa was held in January 2009 in Nairobi, Kenya. The workshop featured expert presentations on key aspects of agrobiodiversity, pointing at the knowledge and skills required in graduates. Workshop participants from 16 African and two European countries identified key issues for teaching and learning agrobiodiversity and outlined a framework for integrating the subject in university curricula. An action plan was developed and a task force was assigned to follow up the workshop recommendations.